Gender features of the midlife crisis (Actual Problems of Psychology in Educational Institutions, 2023)
This article analyzes the general features of the midlife crisis.Among the main regularities of the course of the mid-life crisis, thefollowing were identified: reassessment of the life plan; search for newmeanings; determination of goals and ways to achieve them, in accordancewith updated life priorities. An attempt was made to identify genderdifferences in experiencing a crisis at the age of 35–48. With the help ofthe «Sense-Life Orientations Test» — (J. Krambo and L. Maholika adaptedby D. A. Leontiev) method, the features of the sense-life orientations ofmiddle-aged men and women were determined.
Keywords: crisis, middle-age crisis, gender characteristics of middle age, meaningful life orientations of middle-aged men and women